2022
DOI: 10.3390/biology11010084
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Application of Methyl Jasmonate Increases Emissions of Volatile Organic Compounds in Pyrenean Oak Trees, Quercus pyrenaica

Abstract: The tri-trophic interactions between plants, insects, and insect predators and parasitoids are often mediated by chemical cues. The attraction to herbivore-induced Plant Volatiles (HIPVs) has been well documented for arthropod predators and parasitoids, and more recently for insectivorous birds. The attraction to plant volatiles induced by the exogenous application of methyl jasmonate (MeJA), a phytohormone typically produced in response to an attack of chewing herbivores, has provided controversial results bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…Alternatively, these compounds could have acted hormonally on the focal plants themselves, causing the release of additional HIPVs or other primed defenses (Heil and Silva Bueno 2007, Ramadan et al 2011, Hagiwara et al 2021, Yu et al 2022). Other studies have applied methyl jasmonate by direct spray instead of through dispenser vials (Mäntylä et al 2014, Mrazova and Sam 2018, Saavedra and Amo 2018b, Amo et al 2022), which may have elicited stronger internal signaling effects and the release of additional HIPVs. While our study did not differentiate between these 2 possibilities, we nevertheless still did not find any difference in methyl jasmonate or methyl salicylate treatments compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, these compounds could have acted hormonally on the focal plants themselves, causing the release of additional HIPVs or other primed defenses (Heil and Silva Bueno 2007, Ramadan et al 2011, Hagiwara et al 2021, Yu et al 2022). Other studies have applied methyl jasmonate by direct spray instead of through dispenser vials (Mäntylä et al 2014, Mrazova and Sam 2018, Saavedra and Amo 2018b, Amo et al 2022), which may have elicited stronger internal signaling effects and the release of additional HIPVs. While our study did not differentiate between these 2 possibilities, we nevertheless still did not find any difference in methyl jasmonate or methyl salicylate treatments compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Studies testing the attractive effects of methyl jasmonate or methyl jasmonate-induced HIPV release on insectivorous birds have yielded conflicting results across different plant species, with some studies finding no effect of methyl jasmonate treatment (Mäntylä et al 2014, Saavedra and Amo 2018b, Nguyen et al 2022), but others showing clearer avian recruitment effects (Mrazova and Sam 2018, Amo et al 2022). In contrast, a lower number of studies using methyl salicylate have shown clearer attractive effects (Rubene et al 2019, Nguyen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation